2003
DOI: 10.2175/193864703784639787
|View full text |Cite
|
Sign up to set email alerts
|

Cogenerate With Digester Gas? With What??

Abstract: The Sanitary District of Decatur, Illinois operates a wastewater treatment plant that utilizes an anaerobic sludge digestion process. The gas produced by the digestion process is collected and used to generate electricity at the plant in a cogeneration system. The cogeneration system's two engines have recently required an increased amount of maintenance and are approaching the end of their useful life. In considering replacement options, the District and Malcolm Pirnie, Inc. analyzed the quality and quantity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The studies performed by Liang and Sheehan (2002) and Enochs et al (2003) evaluated emerging technologies for siloxanes removal such as activated carbon filter systems, synthetic resins, condensation/refrigeration, liquid absorbents, and membrane technology. Both studies concluded that activated carbon filters are best siloxane removal system available because of their ease of implementation, performance capabilities, operational history, installation costs, and maintenance requirements.…”
Section: Activated Carbon Filtermentioning
confidence: 99%
See 2 more Smart Citations
“…The studies performed by Liang and Sheehan (2002) and Enochs et al (2003) evaluated emerging technologies for siloxanes removal such as activated carbon filter systems, synthetic resins, condensation/refrigeration, liquid absorbents, and membrane technology. Both studies concluded that activated carbon filters are best siloxane removal system available because of their ease of implementation, performance capabilities, operational history, installation costs, and maintenance requirements.…”
Section: Activated Carbon Filtermentioning
confidence: 99%
“…Since then, there have been 47 additional SAG™ systems installations in the U.S. (Tower, 2003b). The installed capital cost of a SAG™ system at the Sanitary District of Decatur (Illinois, U.S.) was about US$ 50,000 (US$ 8.20 per m 3 /d capacity flow or US$ 0.031 per gpd capacity flow); its annual operating cost is estimated to be approximately US$ 9,500/yr (US$ 1.55 per m 3 /d capacity flow per yr or US$ 0.006 per gpd capacity flow per yr) (Enochs et al, 2003).…”
Section: Activated Carbon Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…Since the bottom-line requirement is removal of siloxane, various forms of activated carbon filtration have been chosen to address siloxane 3 . Unfortunately, activated carbon filtration of digester gas also subjects the rather limited adsorption sites to heavy hydrogen sulfide loading that will result in frequent bed regeneration or replacement intervals and considerable operating cost.…”
Section: Gas Treatmentmentioning
confidence: 99%